Training modules for measurement and data acquisition (module view) - Mejia, I; Gutiérrez, J; Moncada, V (Nexo Revista Científica, 2010)
The Project proposes a design for the implementation of a laboratory tool which aims to contribute toward a solution for the current defecit in methods of student training in electrical engineering in the National University of Engineering. As well as in the area of industrial automatization, specifically in the acquisition and processing of images. The system of artificial vision to be implemented has the capacity to allow for different practical studies in the areas of acquisition and image processing. Included in the application are the following: the detection of manufacturing faults in different products, such as, electrical fuses integrated within HSIP capping, circular objects etc; Information on bar codes; Visual character recognition; Visual oversight of analogical, digital indicators (LCD). The hardware components meet the regulation standards IEEE 1394 (Sensor and Acquisition Hardware) and the processing software is implemented using the platform of LabVIEW. Different scenarios have been incorporated into the hardware component. These include, camera position, amount of illumination in relation to the object under scrutiny and guaranteed acquisition of data with which to evaluate and compare use and application. The software exemplifies the different methods and algorithms of image processing, recreating applications which are typically found in Nicaraguan Industry. To ensure the greatest advantage and adequate use, the necessary documentation regarding use and maintainance of the system is included. Keywords: Viewing machines; image processing; quality control; data acquisition. DOI: 10.5377/nexo.v22i2.43 Nexo: Revista Científica Vol. 22, No. 02, pp.56-60/Diciembre 2009